Food Security Policy: A Model Line of Food Security Policy in Indonesia - Bambang Irawan; Indra Kertati; Rahmat Salam; Muhammad Bagus Adi Wicaksono; Irma Rachmawati Maruf (Universitas Dharma Wacana, 2022)
This research was carried out to see how food security policy is by looking at how much per capita consumption is carried out by lowland rice farmers within one year. With this, it can be known when rice farmers experience rice shortages and cannot afford to buy rice and how to overcome this food security policy problem. This study will collect quantitative and qualitative data relating to food production. Analysis of data utilizing both quantitative and qualitative methods. Food Security policy Lines and Farmers' Fear Ratio: Quantitative and Qualitative Modeling Using this Food Security policy Line Model, rice farmer families' food security policy will be characterized as either robust or weak. Calculating the Farmer Fear Ratio in order to evaluate if farmers are pessimistic or optimistic about the fulfillment of rice consumption needs. This study found that the amount of rice consumption in village X for rice farmers reached 121 kg of rice per capita per year, while in village Y, it reached 185 kg per capita per year. In the meantime, when rice farmers face rice shortages and cannot afford to purchase rice in the market, they borrow rice from mills. In village X, the food security policy line is over 1, while in village Y it is below 1. This indicates that village X has a higher level of food security policy than village Y.